45 Role of Natriuretic Peptides in Screening of Cardiac Dysfunction in Older Patients with Type-2 Dibetes Mellitus. A Report from Sica-diabetes Study (FP7/2007–2013/241558). (31st May 2014) - Fazlalizadeh, Helen; Pellicori, Pierpaolo; Kazmi, Syed; Zhang, Jufen; Clark, Andrew; Saveliych, Bokyi; Warden, John; Byass, T; Henderson, C; Freeman, R; Cleland, John GF
Abstract : Purpose: Type-2 diabetes mellitus (T2DM) is risk factor for developing cardiac dysfunction and heart failure. The plasma concentration of amino-terminal pro-brain natriuretic peptide (NT-proBNP) could be a simple tool for screening for cardiac dysfunction amongst older patients with T2DM. Method: Patients receiving treatment for T2DM for at least 12 months, aged >40 years and not already known to have heart or renal failure were invited to complete a symptom questionnaire and to have NT-proBNP measuredas part of their annual check-up in primary care. Patients also had a physical examination, routine laboratory tests and were tested for neuropathy and retinopathy. All patients with increased NT-proBNP values and a sample of others was invited to attend for further cardiac investigations. Results: Of 1224 patients screened, the median age was 65 (IQR: 58–72) years and 520 (42%) were women. NT-proBNP was >500 ng/L in 54 (4%), 250–500 ng/L in 83 (7%), 125–250 ng/L in 212 (17%), 50–125 ng/L in 424 (34%) and <50ng/L in 451 (37%). Patients with higher NT-proBNP had lower body mass index, smaller waist circumference and higher serum creatinine but had similar heart rate and blood pressure. Of the 54 patients with values >500 ng/L, 43% had symptoms suggesting heart failure, and 20% had serum creatinine >150 umol/L (median: 100 (IQR: 81–140) µmol/L). In patients with NT-proBNP >500 ng/L, 2% had serum creatinine >150 umol/L (median: 77(65–91) µmol/L) and 19% had maculopathy or Grade 2 or worse retinopathy. Onechocardiography, all but two patients had major cardiac dysfunction; 24% had left ventricular ejection fraction <50%, 78% a dilated left atrium >38 mm, 30% had elevated systolic pulmonary artery pressures (>40 mmHg) and 42% patients were in atrial fibrillation. During a median follow-up of 436 (IQR: 334–503) days, the percentage of patients with a cardiovascular admission rose progressively from 8%, 13%, 19% to 28% and all-cause mortality from 0.6%, 0.6%, 1.2%, 3.9% to 9.8% for each of the NT-proBNP strata. Conclusions: NT-proBNP is a simple method of screening for cardiac dysfunction inT2DM. A high proportion of those with elevated values have a dilated left atrium and pulmonary hypertension possibly reflecting left ventricular diastolic dysfunction.